Real-world insights on nutritional awareness and behaviors among preconception and pregnant women in three Asia Pacific countries - Furness, Denise; Huynh, Nguyen Khanh Trang; Kaufmann, Ligaya; Liu, Jue; Nguyen, Thi Bich Ngoc; Schaefer, Ella; Tan, Lucy; Yau, Ching Danica; Yu, Qi (Frontiers in Global Women's Health, 2024)
Introduction In many parts of Asia Pacific (APAC), insufficient intake of micronutrients that are important for conception and pregnancy remains a prevalent issue among women of reproductive age. It is crucial to gain insights into women's nutritional awareness and nutrition-related behaviors, as well as how these relate to their health literacy (HL). This understanding can help identify gaps and guide the development of appropriate intervention strategies. However, there appears to be limited relevant data available for the APAC region. We therefore examined nutritional awareness and behaviors among preconception and pregnant women in three APAC countries, and explored how these were related to women's HL. Methods Cross-sectional online surveys were conducted among preconception (i.e., planning to conceive within the next 12 months or currently trying to conceive) and pregnant women in Australia (N = 624), China (N = 600), and Vietnam (N = 300). The survey questionnaire included a validated tool for HL (Newest Vital Sign) and questions to examine awareness and behaviors relating to healthy eating and prenatal supplementation during preconception and pregnancy. Results Despite recommendations for a quality diet complemented by appropriate supplementation during preconception and pregnancy, many respondents in each country were not aware of the specific impact of adequate nutrition during these stages. While many respondents reported changes in their diet to eat more healthily during preconception and pregnancy, a substantial proportion were not taking prenatal supplements. Higher HL was related to greater nutritional awareness and higher use of prenatal supplements. Discussion Our findings suggest that there are gaps in nutritional awareness and practices of many preconception or pregnant women in the three countries. Interventions to improve HL would be valuable to complement conventional knowledge-centric nutrition education, and enhance understanding and empower women to adopt appropriate nutritional practices throughout their preconception/pregnancy journey.